Characterization of Diversity of Bradyrhizobia on Cowpea in Iraq Reveals Unusual Strain Characteristics (Atlas Journal of Biology, 2017)
Rhizobium-legume symbiosis is considered as one of the most well established symbiotic nitrogen fixing system for agronomic studies. Association between legumes and rhizobia results in the formation of root nodules where symbiotic nitrogen fixation occurs. The current study aimed to authenticate 110 isolates from 20 sites belonging to 10 governorates in Iraq, tested their capacity of nodulation with cowpea and classified them depending on the phenotype and genotype presented by sequence analysis of 16S rRNA. To fulfill these goals, many approaches have been implemented such as Authentication Tests, Bromothymol Blue Reaction, Colony Size and Morphology, Antibiotic Test, Sequencing of 16S rRNA and Phylogenetic analysis. This study provides an easy way to classify the Bradyrhizobia sp. strains by genotype analysis depending on the phenotypes (i.e. motility and colony size) by sample preservation and high quality DNA isolation from environmental soil samples followed by 16S rRNA sequencing. This molecular technique has demonstrated the usefulness of these methods, easy technologies, and their applications to microbiome analysis and environmental science. Interestingly, a group of Bradyrhizobia identified in the current study was able to secrete acidic products before switching and starting to secrete alkali products after 1, 2 and 3 days. This is an unusual phenotype observed within rhizobia strains.